Management of metastatic endometrial cancer: physicians’ choices beyond the first line after approval of checkpoint inhibitors - Arezzo, Francesca; Giannone, Gaia; Castaldo, Daniele; Scotto, Giulia; Tuninetti, Valentina; Turinetto, Margherita; Bartoletti, Michele; Mammoliti, Serafina; Artioli, Grazia; Mangili, Giorgia; Salutari, Vanda; Lorusso, Domenica; et al. (Frontiers in Oncology, 2023)
Introduction Endometrial cancer (EC) represents 3.4% of all newly diagnosed cancer cases and is responsible for 2.1% of all cancer-related deaths. Approximately 10%–15% of women with EC are diagnosed with advanced-stage disease, resulting in a reported 5-year survival rate of only 17% for those with distant metastases. A better understanding of its molecular features has ushered in a new era of immunotherapy for the treatment of EC, allowing for alternative therapeutic approaches, even in cases of advanced disease. Methods We administered a multi-choice online survey for Multicenter Italian Trials in Ovarian cancer and gynecologic malignancies (MITO) members. The questionnaire was available for 2 months, starting in October 2022. Our objective was to evaluate the current attitude of incorporating molecular characterization of EC into routine clinical practice, appraise the implementation of newly available therapies, and compare the outcomes with the previous survey conducted in April–May 2021 to ascertain the actual changes that have transpired during this recent time period. Results The availability of molecular classification in Italian centers has changed in 1 year. Seventy-five percent of centers performed the molecular classification compared with 55.6% of the previous survey. Although this percentage has increased, only 18% performed all the tests. Significant changes have occurred in the administration of new treatments in EC patients in MITO centers. In 2022, 82.1% of the centers administrated dostarlimab in recurrent or advanced MMR-deficient (dMMR) EC experiencing disease progression after platinum-based chemotherapy regimens, compared to only 24.4% in 2021. In 2022, 85.7% of the centers already administrated the pembrolizumab plus lenvatinib combination as a second-line therapy for MMR-proficient (pMMR) patients with advanced or recurrent EC who had progressed from first-line platinum-based therapy. Conclusion Both the therapeutic and diagnostic scenarios have changed over the last couple of years in MITO centers, with an increased prescription of immune checkpoint inhibitors and use of the molecular classification.